The Effect of Four Types of Broad-Leaved Trees on Soil C and N Storage and Mineralization in Forest Areas of Noor City - F. S. Tarighat; Y. Kooch (علوم آب و خاک, 2018)
The effect of broad-leaved forest trees (Alnus glotinusa, Ulmus glabra, Popolus caspica and Parrotia persica) and their canopy position on soil C and N storage and mineraization in the plain forest areas of Noor was investigated. Soil samples were taken from two positions (near and away from the main stem) with the microplots of 30×30×15 cm. Litter (C and N), soil physical (bulk density, texture and water content), chemical (pH, EC, organic C, total N and available Ca), biochemical and biological (N mineralization and microbial respiration) characteristics were measured at the laboratory. Carbon mineralization rate (CMR) was calculated using the equation [incubation time period (hour) ×soil volume (gr) / CO2 amount (mol C)]. Soil C and N storage (ton/ha) was calculated by C and N contents, bulk density, and the soil sampling depth. The results showed that there was no significant difference between the C storage under the studied tree spcies, whereas N storage presented significantly greater amounts, under Alnus glotinusa (0.79 ton/ha) rather than Ulmus glabra, Popolus caspica and Parrotia persica (0.69, 0.45 and 0.21 ton/ha, respectively). The higher values of soil C (0.001 mol C/kg) and N (0.3 ml N/kg) mineralization were significantly recorded under Alnus glotinusa instead of tree species. Soil C and N storage and mineralization process were not affected by the sampling positions. According to the results, soil C and N storage and mineralization were influenced by litter quality and soil chemistry.